Polymer-Based Wound Dressings Loaded with Essential Oil for the Treatment of Wounds: A Review - Bruna Michele A. de B. Buriti; Pablo Luis B. Figueiredo; Marcele Fonseca Passos; Joyce Kelly R. da Silva (MDPI AG, 2024)
Wound healing can result in complex problems, and discovering an effective method to improve the healing process is essential. Polymeric biomaterials have structures similar to those identified in the extracellular matrix of the tissue to be regenerated and also avoid chronic inflammation, and immunological reactions. To obtain smart and effective dressings, bioactive agents, such as essential oils, are also used to promote a wide range of biological properties, which can accelerate the healing process. Therefore, we intend to explore advances in the potential for applying hybrid materials in wound healing. For this, fifty scientific articles dated from 2010 to 2023 were investigated using the Web of Science, Scopus, Science Direct, and PubMed databases. The principles of the healing process, use of polymers, type and properties of essential oils and processing techniques, and characteristics of dressings were identified. Thus, the plants Syzygium romanticum or Eugenia caryophyllata, Origanum vulgare, and Cinnamomum zeylanicum present prospects for application in clinical trials due to their proven effects on wound healing and reducing the incidence of inflammatory cells in the site of injury. The antimicrobial effect of essential oils is mainly due to polyphenols and terpenes such as eugenol, cinnamaldehyde, carvacrol, and thymol.